If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2y = 66 Solving 7x + 2y = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 7x + 2y + -2y = 66 + -2y Combine like terms: 2y + -2y = 0 7x + 0 = 66 + -2y 7x = 66 + -2y Divide each side by '7'. x = 9.428571429 + -0.2857142857y Simplifying x = 9.428571429 + -0.2857142857y
| -16x^2+56x-24= | | 2(1x+3)-2=8+2x | | x^3+x=23 | | 4u-9=67 | | 12k=-144 | | 2c+1+80+113=180 | | 72+B^2=10000 | | 4-9x=-67 | | (16x+3)(18x-5)=0 | | d=12-(11-4d) | | Z+(-5)whenz=9 | | 180=2x+x+y+5 | | 1+2(1b+6)=5(1b-1) | | 4a+2a=50 | | 0=5+x | | 2x+142=90 | | 7+7n=6n | | 3=-1/9[-3]-2 | | (8v-40)(v^2+9v+14)=0 | | 4x^2-1x-5=O | | 7r-3r-13r=3 | | 1-6=178 | | 180=x+y+5+y | | -5=m-5 | | -0.7x+8.23=-0.2x+7.23 | | 16=n/11 | | 5x+2+3x-5=22 | | x/2-16=53 | | Y^2+x^2-2y+8x-83=0 | | -18y^6/-2y^2 | | ln(x+6)=4+lnx | | Y-9=177 |